Bacterial Community Composition in Brazilian Anthrosols and Adjacent Soils Characterized Using Culturing and Molecular Identification - O'Neill, B; Grossman, J; Tsai, M. T; Gomes, J. E; Lehmann, J; Peterson, J; Neves, E; Thies, J. E (Microbial ecology, 2009)
Microbial community composition was examined in two soil types, Anthrosols and adjacent soils, sampled from three locations in the Brazilian Amazon. The Anthrosols, also known as Amazonian dark earths, are highly fertile soils that are a legacy of pre-Columbian settlement. Both Anthrosols and adjacent soils are derived from the same parent material and subject to the same environmental conditions, including rainfall and temperature; however, the Anthrosols contain high levels of charcoal-like black carbon from which they derive their dark color. The Anthrosols typically have higher cation exchange capacity, higher pH, and higher phosphorus and calcium contents. We used culture media prepared from soil extracts to isolate bacteria unique to the two soil types and then sequenced their 16S rRNA genes to determine their phylogenetic placement. Higher numbers of culturable bacteria, by over two orders of magnitude at the deepest sampling depths, were counted in the Anthrosols. Sequences of bacteria isolated on soil extract media yielded five possible new bacterial families. Also, a higher number of families in the bacteria were represented by isolates from the deeper soil depths in the Anthrosols. Higher bacterial populations and a greater diversity of isolates were found in all of the Anthrosols, to a depth of up to 1 m, compared to adjacent soils located within 50-500 m of their associated Anthrosols. Compared to standard culture media, soil extract media revealed diverse soil microbial populations adapted to the unique biochemistry and physiological ecology of these Anthrosols.